1999
DOI: 10.1098/rspb.1999.0746
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal diseases in bottlenose dolphins: impacts of natural and anthropogenic factors

Abstract: Experimental studies have highlighted the potential in£uence of contaminants on marine mammal immune function and anthropogenic contaminants are commonly believed to in£uence the development of diseases observed in the wild. However, estimates of the impact of contaminants on wild populations are constrained by uncertainty over natural variation in disease patterns under di¡erent environmental conditions. We used photographic techniques to compare levels of epidermal disease in ten coastal populations of bottl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
117
2
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(122 citation statements)
references
References 27 publications
2
117
2
1
Order By: Relevance
“…Nonetheless, the general appearance of some skin conditions can be used to assess the likelihood that they are indicative of a particular etiology. Although Wilson et al (1999) used different categorizations to evaluate skin conditions, their results indicated a similarly high incidence within geographically separated bottlenose dolphin populations, incidence ranging between 67% in Florida and 100% in England. Our study population falls within the higher values (90%) found by Wilson and colleagues, supporting the hypothesis that skin conditions are a geographically widespread phenomenon in bottlenose dolphins.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, the general appearance of some skin conditions can be used to assess the likelihood that they are indicative of a particular etiology. Although Wilson et al (1999) used different categorizations to evaluate skin conditions, their results indicated a similarly high incidence within geographically separated bottlenose dolphin populations, incidence ranging between 67% in Florida and 100% in England. Our study population falls within the higher values (90%) found by Wilson and colleagues, supporting the hypothesis that skin conditions are a geographically widespread phenomenon in bottlenose dolphins.…”
Section: Discussionmentioning
confidence: 99%
“…Our study population falls within the higher values (90%) found by Wilson and colleagues, supporting the hypothesis that skin conditions are a geographically widespread phenomenon in bottlenose dolphins. The variability in prevalence and appearance of these conditions may depend on local environmental variables such as water temperature and salinity, and/or the presence of other 'stressors' such as water contamination (Wilson et al 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They may be caused by viruses, bacteria, fungi and protozoans and appear to be occurring more frequently in recent years . Their emergence and severity seem, in some cases, to be related to natural and anthropogenic factors such as water quality degradation and inland water inputs (Wilson et al 1999, Reif et al 2006, Van Bressem et al 2007, 2009.…”
Section: Introductionmentioning
confidence: 99%
“…Ten coastal populations of bottlenose dolphins served in a photographic study that compared levels of epidermal disease among populations exposed to a wide range of natural and anthropogenic conditions [33]. It was found that epidermal lesions were common in all populations.…”
Section: Case Studies Of Skin Lesions In Cetaceans -The Signs?mentioning
confidence: 99%